2016
DOI: 10.1007/s10853-016-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal melt spinning of polyvinylpyrrolidone (PVP)/triacontene copolymer fibres

Abstract: Polyvinylpyrrolidone/1-triacontene (PVP/TA) copolymer fibre webs produced by centrifugal melt spinning were studied to determine the influence of jet rotation speed on morphology and internal structure as well as their potential utility as adsorbent capture media for disperse dye effluents. Fibres were produced at 72°C with jet head rotation speeds from 7000 to 15,000 r min -1 . The fibres were characterised by means of SEM, XRD and DSC. Adsorption behaviour was investigated by means of an isothermal bottle po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 42 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…O'Haire et al 43 reported a reduction of fiber diameters with increasing rotational speed, but in their case PVP polymer was used. However, the authors did not submit standard deviations for single‐diameter fibers, and in this case the standard deviations are the decisive factor of individual measurements.…”
Section: Resultsmentioning
confidence: 99%
“…O'Haire et al 43 reported a reduction of fiber diameters with increasing rotational speed, but in their case PVP polymer was used. However, the authors did not submit standard deviations for single‐diameter fibers, and in this case the standard deviations are the decisive factor of individual measurements.…”
Section: Resultsmentioning
confidence: 99%
“…17 In recent years, fiber-based materials fabricated by centrifugal spinning have been used in various fields, such as energy storage, thermal insulation, and medical dressings. [18][19][20][21][22][23] Moreover, the productivity of centrifugal spinning exceeds 1 gÁmin À1 per nozzle, which is significantly higher than that of laboratory-scale electrospinning (0.1 gÁh À1 ). 24 However, most centrifugal spinning equipment can only collect fibers using columns.…”
Section: Introductionmentioning
confidence: 95%
“…PVP is not suitable for thermoplastic processing in the usual manner since it is very brittle in pure form, which is why plasticizers are added to make PVP-based films [6,7]. A recent shift has been to utilize natural or biodegradable plasticizers with low toxicity and good compatibility [8]; examples compatible with PVP and water include glycerol, sorbitol, mannitol, arabic gum, polyethylene and glycol [9][10][11].…”
Section: Introductionmentioning
confidence: 99%